The macroeconomic determinants of exchange rate volatility in Malaysia / Mohd Zulakmal Mohd Nor - Mohd Nor, Mohd Zulakmal (Faculty of Business and Management, 2015)
This study is done to investigate and analyze the macroeconomic determinants of exchange rate volatility in Malaysia. The financial data used in this study is to determine what macroeconomic factors affect the exchange rates going in an upward or downward direction (volatile). The variables considered in this study are national income, inflation, government debt, interest rate and money supply. The sample of this study comprises of 56 quarters of both the dependant and independent variables on a yearly basis over a 14 year period from 2001-2014. The data can be obtained from Data Stream, EUI Database and World Data Bank. Interactive software package, E-views, will be used for regression analyzing the data that have been collected. The variables are basically from previous research papers that are related to the determinants of foreign exchange. The results of this research would determine which financial data variables have a significant effect towards exchange rate volatility in Malaysia.